Development of Social-Emotional Skills in Group B Through Guided Role Play: A PTK Study at Sejahtera Mandiri Early Childhood Education Center: Pengembangan Keterampilan Sosial-Emosional Kelompok B Melalui Bermain Peran Terbimbing: Studi PTK Di Paud Sejahtera Mandiri - Emi Suryani; Della Amrina Yusra (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
Social-emotional development is a fundamental aspect of early childhood that influences future academic success and mental well-being. This study aimed to improve the social-emotional skills of Group B children at PAUD Sejahtera Mandiri through guided role-playing. This Classroom Action Research (PTK) was conducted in two cycles using the Kemmis and McTaggart model, involving 15 children (8 boys and 7 girls) aged 5-6 years. Data were collected through observation, field notes, and documentation, then analyzed using qualitative descriptive and quantitative percentage techniques. The results showed that before the intervention, only 20% of children achieved the expected developmental milestones. In Cycle I, guided role-playing with the theme